The Public Lives of Ancient Women (500 BCE-650 CE) - Dirven, Lucinda,; Icks, Martijn,; Remijsen, Sofie, (Classical Studies E-Books Online, Collection 2023., 2023)
Building on the important work by Hemelrijk, this volume endeavours to bring ancient women out of the domestic sphere and to examine their presence and activities in the public domain, for example as rulers, patrons, priestesses, wives, athletes and pilgrims. Covering the period 500 BCE to 650 CE and ranging across the Mediterranean and beyond, it fruitfully employs a great variety of source types and thematic approaches to argue that women in the ancient world were active in many parts of the public domain, including the civic, the religious and at times even the political and military spheres.